2013
DOI: 10.1002/ijch.201200094
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Synergistic Data Tools for Biological Scrutiny

Abstract: A network of biological databases is reviewed, supplying a framework for studies of human genes and the association of their genomic variations with human phenotypes. The network is composed of GeneCards, the human gene compendium, which provides comprehensive information on all known and predicted human genes, along with its suite members GeneDecks and GeneLoc. Two databases are shown that address genes and variations focusing on olfactory reception (HORDE) and transduction (GOSdb). In the realm of disease sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Sp1 has zinc finger motifs by which it binds directly to DNA at the GC box element by the established consensus sequence 5Ј-GGGGCGGGG or (G/T)-GGGCGG(G/A)(G/A)(C/T)-3Ј (11). Multiple studies have confirmed that mutation of this consensus sequence leads to reduced promoter activation and expression of target genes (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Sp1 has zinc finger motifs by which it binds directly to DNA at the GC box element by the established consensus sequence 5Ј-GGGGCGGGG or (G/T)-GGGCGG(G/A)(G/A)(C/T)-3Ј (11). Multiple studies have confirmed that mutation of this consensus sequence leads to reduced promoter activation and expression of target genes (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Molecular structure of doi: 10.7243/2052-434X-4-1 the fusion between in PDGFRα and ETV6 was examined in a few cases of t(4;12). Curtis et al, [22] reported an MPN with eosinophilia and t(4;12) in which ETV6 was translocated to the 5'-of an intact WW domain of PDGFRα; this patient responded to imatinib. Yoshida et al, [40] reported an another case in which ETV6 fused to the C-terminus of PDGFRα and the patient did not respond to imatinib.…”
Section: Discussionmentioning
confidence: 87%
“…Evaluation of gene function for each of these genes was conducted using GeneCards encyclopedia (www.genecards.org), and annotated by the area of interest utilizing UCSC, Ensemble, Uniprot, MGI mutation, GO/KEGG pathway, OMIM diseases, and MalaCards diseases [22]. This evaluation indicated that 6 genes, E2F3, GMNN, CHTF18, TELO2, CCNF and PKMYT1 have a cell cycle function; 7 genes, TXNDC5, SOX4, PRL, AXIN1, ZNF598, NRG3 and DNAJA3 have a function related to apoptosis; 8 genes, DEK, ID4, TRIM38, ZMIZ1, IL32, CREBBP, GLIS2 and PGP have been reported to be related to established leukemic entities; and 8 genes, PKMYT1, IL32, RIPK1, PRPF4B, NRG3, MLST8, PGP and PDPK1 have been linked to tyrosine kinase signaling pathways.…”
Section: Cytogenetics and Fishmentioning
confidence: 99%
“…For the above members of the UPR, a summary of the gene/protein names and their synonyms as well as their primary subcellular localization was compiled from www.genecards.org (Olender et al 2013) and is presented in Table 2.…”
Section: Discussionmentioning
confidence: 99%